March 26, 2017

Post a New Question

Posted by on .

5(4r-3c)-2(7r-9c)=0 solve for r

This is all I know how to do and don't know if it's even right. Or what to do from here.

5(4r-3c)-2(7r-9c)=0 solve for r

  • Maath - ,

    see the post above this, follow the same steps

  • Maath - ,

    this is the steps:

    so for my final answer I got r=c/2 is that correct?

  • Maath - ,

    close ...

    from your second last line
    6r + 3c = 0
    6r = - 3c
    r = -c/2

    btw, I am glad you caught your error in the steps of your original at the top,
    where did the -11c come from?

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question